Local B1+ shimming for prostate imaging with transceiver arrays at 7T based on subject-dependent transmit phase measurements - Metzger, Gregory J.; Snyder, Carl; Akgun, Can; Vaughan, Tommy; Ugurbil, Kamil; Van de Moortele, Pierre-Francois (Magnetic resonance in medicine, 2008)
High‐quality prostate images were obtained with transceiver arrays at 7T after performing subject‐dependent local transmit B1 (B1+) shimming to minimize B1+ losses resulting from destructive interferences. B1+ shimming was performed by altering the input phase of individual RF channels based on relative B1+ phase maps rapidly obtained in vivo for each channel of an eight‐element stripline coil. The relative transmit phases needed to maximize B1+ coherence within a limited region around the prostate greatly differed from those dictated by coil geometry and were highly subject‐dependent. A set of transmit phases determined by B1+ shimming provided a gain in transmit efficiency of 4.2 ± 2.7 in the prostate when compared to the standard transmit phases determined by coil geometry. This increased efficiency resulted in large reductions in required RF power for a given flip angle in the prostate which, when accounted for in modeling studies, resulted in significant reductions of local specific absorption rates. Additionally, B1+ shimming decreased B1+ nonuniformity within the prostate from (24 ± 9%) to (5 ± 4%). This study demonstrates the tremendous impact of fast local B1+ phase shimming on ultrahigh magnetic field body imaging. Magn Reson Med 59:396–409, 2008. © 2008 Wiley‐Liss, Inc.